Combination of PDT and NOPDT with a Tailored BODIPY Derivative - Loretta Lazzarato; Elena Gazzano; Marco Blangetti; Aurore Fraix; Federica Sodano; Giulia Maria Picone; Roberta Fruttero; Alberto Gasco; Chiara Riganti; Salvatore Sortino (MDPI AG, 2019)
The engineering of photosensitizers (PS) for photodynamic therapy (PDT) with nitric oxide (NO) photodonors (NOPD) is broadening the horizons for new and yet to be fully explored unconventional anticancer treatment modalities that are entirely controlled by light stimuli. In this work, we report a tailored boron-dipyrromethene (BODIPY) derivative that acts as a PS and a NOPD simultaneously upon single photon excitation with highly biocompatible green light. The photogeneration of the two key species for PDT and NOPDT, singlet oxygen (1O2) and NO, has been demonstrated by their direct detection, while the formation of NO is shown not to be dependent on the presence of oxygen. Biological studies carried out using A375 and SKMEL28 cancer cell lines, with the aid of suitable model compounds that are based on the same BODIPY light harvesting core, unambiguously reveal the combined action of 1O2 and NO in inducing amplified cancer cell mortality exclusively under irradiation with visible green light.